Internalising Sharia Economic Law for Sustainable Marine Tourism: Environmental Mitigation Practices on Pahawang Island - Hidayat Darussalam; Risfiana Mayangsari; Rasyid Tanjung; Fitri Kurniawati; Lukas Meier Keller (Journal of Nusantara Economy, 2026)
The rapid growth of marine tourism on Pahawang Island has generated significant economic opportunities while simultaneously intensifying ecological degradation due to tourism activities that exceed the island’s environmental carrying capacity. This study aims to examine how the principles of Sharia Economic Law can be internalised into sustainable marine tourism management to strengthen environmental impact mitigation and ensure long-term ecosystem resilience. A qualitative field research design with a case study approach was employed. Data were collected through in-depth interviews with government officials, tourism business operators, Tourism Awareness Group (POKDARWIS) members, local community leaders, and visitors, complemented by participatory observation and documentary analysis. The data were analysed using an interactive thematic analysis involving data reduction, categorisation, interpretation, and triangulation to enhance credibility. The findings reveal that ecosystem degradation is primarily driven by the dominance of short-term economic interests, weak enforcement of environmental regulations, fragmented stakeholder coordination, and the limited integration of ecological ethics into tourism governance. The study demonstrates that internalising Sharia Economic Law through the framework of Maqashid Shariah provides a normative and operational foundation for sustainable tourism governance. This framework includes environmentally oriented zoning based on hifzh al-bi'ah (environmental protection), transparent digital management of environmental restoration funds, mandatory environmental codes of conduct for tourists, and community-based conservation supported by Islamic ethical values. In addition, a collaborative triple helix governance model involving government institutions, POKDARWIS as the hisbah supervisory mechanism, and local communities as conservation partners significantly enhances environmental stewardship and policy implementation. This research contributes to the development of contemporary Sharia Economic Law by extending its application beyond commercial transactions into environmental governance, offering an integrative legal framework that harmonises economic development, ecological sustainability, and the Islamic principle of khilafah to achieve sustainable welfare in coastal tourism destinations.